Mechanisms of OECD governance international incentives for national policy-making? - Martens, Kerstin; Jakobi, Anja P. (Oxford : Oxford University Press, 2010)
'Mechanisms of OECD Governance' analyses the influential but under-studied Organisation for Economic Co-operation and Development (OECD). It explores its role in political processes through various case studies in a variety of policy fields and provides a current and wide-ranging analysis of this organization.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed Sept. 7, 2010).
Keywords: Organisation for Economic Co-operation and Development; Policy sciences; Organisation for Economic Co-operation and Development -- Case studies; Policy sciences -- Case studies